Key Steps Aimed at Elimination of Conflict of Interests in Participant Groups in Customer Value Chains While Pursuing Company Assortment Policy - K. M. Ilyenkova (Вестник Российского экономического университета имени Г. В. Плеханова)
The article deals with the problem of pursuing company assortment policy, which is aimed at meeting buyers’ needs by joint creation of customer value. Within the frames of this approach the author analyzes existing concepts of building delivery chains and substantiates the use of the concept of building delivery chains from the customer. The role of category management in the context of relation marketing is shown. Participant groups of building customer value chains are identified and the system of their interrelations is demonstrated as the most important element of assortment policy effectiveness. The author puts forward a hypothesis about conflict of interests of participants in customer value chains, in spite of the common goal, i.e. maximum satisfaction of buyers’ needs. On this basis the preconditions of such conflicts of interests in these groups are investigated and steps aimed at their elimination are proposed, whose implementation can raise effectiveness of partner interrelations and therefore, efficiency of company assortment policy targeted at meeting customer needs.